(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: Different educational approaches might lead to different levels of understanding among diabetics. The present study compared the effectiveness of self-learning module (SLM) versus use of power point presentation (PPT) on the knowledge of diet among type II diabetes patients (T2DM). Methodology: This was a quasi-experimental study with pre and post-test design, conducted in the community setting. 85 T2DM patients each were randomly allocated to either SLM or PPT and 170 were controls without intervention. A pre-tested semi-structured questionnaire assessed knowledge on diet and nutrition during baseline (pre-test) and 6 months after intervention (post-test). Changes in knowledge after intervention was assessed using X2, Mc Nemar, paired ‘t’ test. p<0.05 was considered as significant. Results: Both SLM and PPT were equally effective in increasing knowledge on the role of diet in diabetes, different food items. PPT was significantly more effective in increasing the mean knowledge score regarding diet in post-test (28.04+7.34) versus SLM (25.07+6.74) (p<0.001). PPT was more effective than SLM on some aspects of diet viz. concept of carbohydrate as energy giving source, sources of carbohydrates (potato and bread), meat as source of protein, “protein” as body builder; good oils (saffola, cannola, olive oil), avoidance of butter; high glycaemic index (GI) foods (glucose, watermelon), medium GI food (muesli, honey, digestive biscuits), low GI (dalia, brown bread, oats), protein as body building food, meat as source of protein, consumption of fibre rich diet. Conclusion: Both SLM and PPT were effective, more so with PPT on several aspects of diet and nutrition among study subjects. Active interaction along with visual presentation of educative material in powerpoint can be considered for educating T2DM patients on diet and nutrition during home visits by health workers.